Review on the mechanism of failure mode based on mechanical performance analysis of brake disc - Dongna Li; Dele Sun; Huigui Xi; Jianfeng Dai (Advances in Mechanical Engineering)
The reliability and efficiency of brake discs are crucial for ensuring the safe operation of vehicles. With the growing demands of industrial applications and technological advancements, the mechanical performance and failure issues of brake discs have garnered extensive attention. To better understand the mechanisms affecting the mechanical performance and failure modes of brake discs, a comprehensive review of the influencing factors on their mechanical properties is presented. This includes an examination of the impact of brake disc structure, materials, and working conditions from both numerical simulation and experimental perspectives. Furthermore, the effects of temperature distribution and stress distribution on different failure modes of brake discs are summarized. Based on thermomechanical coupling theory, the failure modes under varying temperature and stress conditions are analyzed. Finally, considering the current research status of brake discs, in-depth mechanical performance analysis and failure mode studies can provide significant theoretical and practical guidance for designing more durable and safer brake discs.